KEPUTUSAN PEMBELIAN PRODUK FASHION PADA E-COMMERCE: PENGARUH FASHION CONSCIOUSNESS, SHOPPING ENJOYMENT, NILAI KONSUMEN - Firda Novia Ardana; Yessy Artanti (STKIP Persada Khatulistiwa Sintang, 2022)
The Covid-19 pandemic has changed consumer behaviour from shopping in person to shopping online. During the pandemic, fashion products are in great demand when shopping online, even if only at home, people still need to appear in an attractive style to keep up with the latest trends. In this case, the researcher examines the effect of fashion consciousness, shopping enjoyment, consumer value on online purchasing decisions in e-commerce fashion. The sample used in this study is 200 with a non-probability sampling technique and included in the type of conclusive research. In this study, the data analysis technique used multiple regression analysis. The study results found that fashion consciousness and consumer value have a significant influence on purchasing decisions. However, shopping enjoyment has no significant effect on purchasing decisions. It shows that fashion consciousness and consumer value have an essential role in influencing buying in fashion e-commerce